VERBAL SENTENCES IN UTETOTO VILLAGE, NANGARORO DISTRICT, NAGEKEO REGENCY, FLORES, NTT - Maria Desidaria Noge (JEE (Journal of English Education), 2017)
This study is aimed at revealing the systems of Utetoto Verbal Sentences. Specifically, this study is concerned on: (i) describing the basic sentence patterns of Utetoto Verbal Sentences, (ii) finding out the similarities and differences between English and Utetoto Verbal Sentences, and (iii) predicting some difficulties of Utetoto Students in learning English. This research was descriptive qualitative research. Robert’s (1958) model was used as research design in describing English. At the first, a need analysis was done in the method of describing the basic sentence patterns, mentioning the main patterns of verbal sentences and other patterns of verbal sentences with some native speakers of Utetoto as main informants who stay in Tanah Utetoto. Based on the result of analysis, it was found that there are many different systems between Utetoto Verbal Sentences and English ones. The basic sentence patterns of Utetoto Verbal Sentences are: Noun Phrase (NP), Verbal Phrase (VP), Adjective Phrase (AP), Numeral Phrase (NuP), Adverb Phraes (AdP), and Prepositional Phrase (PP). By contrasting both languages, it found the differences between the native language and the target language. Based on the differences between Utetoto and English system, it can be predicted some difficulties of Utetoto students in learning English.